Bidirectional Violence Is Associated with Poor Engagement in HIV Care and Treatment in Malawian Couples. Issue 7 (April 2022) - Conroy, Amy A.; Leddy, Anna M.; Darbes, Lynae A.; Neilands, Torsten B.; Mkandawire, James; Stephenson, Rob
Growing evidence suggests that intimate partner violence (IPV) is a barrier to engagement in HIV care. Bidirectional IPV—being both a perpetrator and victim—may be the most common pattern of IPV, yet no research has examined its effect on engagement in care, which could identify couples in most need of interventions. Married couples ( N = 211) with at least one partner on antiretroviral therapy were recruited from HIV clinic waiting rooms in Zomba, Malawi. Partners completed separate surveys on physical, sexual, and emotional IPV, medication adherence, and appointment attendance. We created categorical variables indicating no violence, perpetrator-only, victim-only, and bidirectional violence. Generalized estimating equation regression models tested for associations between IPV and engagement in care. The bidirectional pattern represented 25.4%, 35.5%, and 34.0% of all physical, sexual, and emotional IPV. Physical IPV victimization-only (adjusted odds ratio [AOR]: 0.28, 95% confidence interval [CI]: 0.08, 0.92) was associated with lower adherence, but the association was stronger for bidirectional physical IPV (AOR: 0.10, 95% CI: 0.02, 0.51). Bidirectional sexual IPV was also associated with lower adherence (AOR: 0.14, 95% CI: 0.02, 0.80). Bidirectional physical IPV (AOR: 4.04, 94% CI: 1.35, 12.14) and emotional IPV (AOR: 3.78, 95% CI: 1.78, 8.05) were associated with missing 1+ appointment. Interventions to address the health effects of bidirectional IPV, which may be greater than victim-only or perpetrator-only IPV, should intervene with both partners to break cycles of violence. Couple-based interventions may be a viable option by intervening on both partners' trauma and aggression simultaneously.